HERBS AND HERBAL PRODUCTS IN ANIMAL NUTRITION AND VETERINARY MEDICINE - Franz, Ch (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Following the trends in human health care towards herbal medicinal products and plant derived dietary supplements also in Veterinary medicine and livestock production an increasing use of herbs, essential oils and plant extracts can be observed. This is not only due to an ethnoveterinarian revival but also based on the fact that a) antibiotic growth promoters are banned in more and more countries all over the world due to the risk of (cross) resistances b) in organic livestock production the use of synthetic drugs is very restricted, and c) many pet animal and horse owners prefer natural products and “soft medicine” Microbial induced diarrhoea remains one of the crucial problems especially in large scale farm animal production. As alternatives to in-feed antibiotics several herbal mixtures and essential oils are promising, showing significant antimicrobial, antioxidant and growth promoting effects. Porcine proliferative entheropathy could be controlled by e.g. carvacrol-rich oregano oil, necrotic enteritis of chicks was successfully prevented by several essential oil compounds. In ruminants some herbal preparations are effective in reduction of methane and ammonia production, which is of high environmental relevance [1]. A number of plants containing bioactive secondary products are used also in health care of horses and pet animals, as e.g. fennel, anis and caraway against bloat and flatulence, tea-tree oil to treat dermatological problems or milk thistle extracts to prevent liver damages. The increasing use of herbs and herbal products is not reduced to Europe and North America, but has an enormous significance and potential all over the world especially where ethnoveterinary knowledge still exists [2]. Phytochemical as well as in-vivo and in-vitro studies will help to exploit these resources for the benefit of humans and animals. [1]Franz, Ch.: Functional Plant Products in Veterinary Medicine and Animal Nutrition. Planta med. 73, 799 (2007) [2] ICS-UNIDO: Medicinal and Aromatic Plants in Veterinary Health Care. Expert Group Meeting Trieste, Italy (2007)